Yoga for a strong & healthy back for beginner to intermediate - Yoga Zone (Firm) (Port Washington, NY : KOCH Vision, 2001)
The exercises taught in these two twenty-minute sessions will strengthen your abdominal muscles, improve your alignment and help you build a stronger back.
DVD.
Keywords: Hatha yoga